Therapeutic potential of Glycyrrhiza polysaccharides in pseudorabies virus infection: immune modulation, antioxidant activity, and gut microbiota restoration - Song, Chunlian; Wei, Qianfei; Shen, Hong; Zhang, Xue; Pan, Deng; Zhang, Zhihui; Zhang, Ying; Yang, Shanhai; Shu, Xianghua (Frontiers in Veterinary Science, 2025)
Aim of the studyThis study aimed to evaluate the protective effects of Glycyrrhiza polysaccharides (GPs) on Pseudorabies virus (PRV)-infected mice and elucidate their mechanisms of action, with a focus on intestinal immunity, oxidative stress, mucosal barrier function, and gut microbiota composition.Materials and methodsGPs were extracted via hot water extraction and ethanol precipitation. Seventy-two SPF-grade male mice were randomly divided into six groups and treated with different doses of GPs or Astragalus polysaccharides (APS), followed by PRV challenge. Clinical parameters, inflammatory cytokines (TNF-α, IL-6, IL-4, IL-10), oxidative stress markers (SOD, CAT, MDA), histopathology, tight junction protein expression (Occludin, ZO-1), sIgA levels, intestinal permeability, viral load, and gut microbiota profiles were assessed.ResultsGP administration significantly alleviated PRV-induced symptoms, reduced mortality and disease activity index, and improved food intake. Medium and high doses notably downregulated TNF-α and IL-6, while upregulating IL-4 and IL-10. Antioxidant activities (SOD, CAT) were enhanced, and MDA levels were decreased. Histological analyses showed recovery from villus atrophy and goblet cell loss. GPs improved tight junction integrity, elevated sIgA, reduced gut permeability and viral burden. Microbiota analysis revealed increased α-diversity, enrichment of Lactobacillus and Bacteroides, and suppression of potential pathogens. Functional predictions suggested GPs influenced immunity- and metabolism-related microbial pathways.ConclusionGPs exert protective effects against PRV-induced intestinal injury by modulating immune and oxidative responses, enhancing mucosal barrier integrity, and rebalancing gut microbiota. These findings support the potential of GPs as a therapeutic agent for viral enteric diseases. To our knowledge, this is the first study to demonstrate the protective role of GPs against PRV infection in vivo. These findings expand current understanding of the antiviral potential of plant-derived polysaccharides and highlight GPs as a promising candidate for the development of novel polysaccharide-based therapeutics for viral enteric diseases.